FCGR2A defines prognostic immune subtypes and drives tumor progression in hepatocellular carcinoma - Zhong, Deyuan; Liang, Yuxin; Yan, Hongtao; Chen, Xing; Chen, YaHui; Ma, Shuoshuo; Su, Yuhao; Wang, Fei; Chen, Xinpei; Yang, Qinyan; Leng, Zhengwei; Wang, Ming; et al. (Frontiers in Immunology, 2025)
BackgroundThe immunosuppressive nature of the HCC tumor microenvironment limits the effectiveness of current immunotherapeutic strategies. Identifying key immune-related regulators is essential for improving patient stratification and therapeutic outcomes.MethodsTranscriptomic data from TCGA and GEO datasets were integrated to screen IRDEGs. Functional enrichment, co-expression, and PPI network analyses were performed to explore the biological context. Consensus clustering based on hub gene expression was used to define immune-related molecular subtypes. Immune infiltration characteristics, immune checkpoint expression, TIDE and IPS scores, and predicted immunotherapy responses were compared. FCGR2A expression was validated in clinical HCC tissues by immunohistochemistry and western blotting. In vitro assays evaluated the effects of FCGR2A knockdown on HCC cell proliferation, migration, and invasion.ResultsA total of 21 IRDEGs were identified, among which FCGR2A was consistently upregulated and associated with poor prognosis. Enrichment analysis indicated significant involvement in immune activation and inflammatory signaling pathways. PPI network analysis identified nine hub genes, including FCGR2A. Consensus clustering revealed two distinct immune-related molecular subtypes with marked differences in immune infiltration patterns, immune checkpoint profiles, TIDE and IPS scores. GSEA demonstrated subtype-specific activation of antigen processing, T cell signaling, and inflammatory pathways. Experimental validation confirmed elevated FCGR2A expression in HCC tissues. Functional assays showed that FCGR2A knockdown significantly inhibited HCC cell proliferation, migration, and invasion.ConclusionsFCGR2A acts as both a prognostic biomarker and an immune regulatory hub in HCC, anchoring a broader gene network that defines immune subtypes and predicts therapeutic responsiveness. Incorporating FCGR2A-based stratification may optimize immunotherapeutic strategies for HCC.